2021
DOI: 10.1021/acsami.1c02943
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer as the Key Parameter Affecting the Color Purity of Thermally Activated Delayed Fluorescence Emitters

Abstract: The key factors determining the emission bandwidth of thermally activated delayed fluorescence (TADF) are investigated by combining computational and experimental approaches. To achieve high internal quantum efficiencies (IQEs) in metal-free organic light emitting diode via TADF, the first triplet (T1) to first singlet (S1) reverse intersystem crossing (rISC) is promoted by configuring molecules in an electron donor-acceptor (D-A) alternation with a large dihedral angle, which results in a small energy gap (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…Building on the previous findings of our group 29,56 and aiming to better understand the connection between analogous D-A and D-A-D molecules, we investigate two isomeric D-A-D TADF emitters comprised of a benzonitrile acceptor and acridine donors attached at the 2,5-or 2,6-positions of the acceptor. Comparison to previously reported D-A materials (facilitated by the self-regulating dihedral angle of DMAC 59 ) allows us to compare these systems with minimal additional complexity introduced by the second D unit. Using a combination of experimental and theoretical methods, we demonstrate that electronic interaction between the donating moieties -modulated by the relative position of each -alters the 3 LE energy and thus also DE ST and TADF performance.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the previous findings of our group 29,56 and aiming to better understand the connection between analogous D-A and D-A-D molecules, we investigate two isomeric D-A-D TADF emitters comprised of a benzonitrile acceptor and acridine donors attached at the 2,5-or 2,6-positions of the acceptor. Comparison to previously reported D-A materials (facilitated by the self-regulating dihedral angle of DMAC 59 ) allows us to compare these systems with minimal additional complexity introduced by the second D unit. Using a combination of experimental and theoretical methods, we demonstrate that electronic interaction between the donating moieties -modulated by the relative position of each -alters the 3 LE energy and thus also DE ST and TADF performance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the balanced CT interactions are also the key parameter to reduce the FWHM. 42 Therefore, a combination of lowering excited state CT interactions through an appropriate donor position and the locking of molecular geometry resulted in deep blue TADF emission with a narrow bandwidth for para -substituted 3BPy- p DTC . In addition, the participation of the T 2 state along with the T 1 state in RISC leads to high device performance for both the emitters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 Further, Kieffer and coworkers demonstrated that balanced CT interactions leading to hole/electron (h/e) overlap represent the key parameter for reducing the FWHM and color purity. 42 The donor substitution at the meta and para positions to the pyridoquinoxaline (PQ) acceptor core significantly affects the CT interactions and optical properties demonstrated by Patra and coworkers. 43 Very few attempts were made to design a conventional TADF emitter with a narrow emission bandwidth in the blue region.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when using the conserved quantities (such as energy, in eV) to compare the FWHM of these molecules (because the dispersion of photons and phonons are described by different physical laws), BN-ICz-1 and BN-ICz-2 show the smallest FWHM values of 0.09 eV (when compared with 0.24 eV for ICz and 0.11 eV for pICz). [14] Therefore, ultra-pure green emission with a dominant peak at ca. 521 nm and CIE coordinates of (0.16, 0.77) could be achieved in BN-ICz-containing solutions.…”
Section: Resultsmentioning
confidence: 99%